The single inverter is affected by electromagnetic interference, and the protection mode - Zhang, Zhenyu (Transactions on Computer Science and Intelligent Systems Research, 2025)
The easiest way to resist electromagnetic interference is to optimize the design to reduce interference. The electromagnetic interference received by a single inverter mainly comes from the influence of electromagnetic radiation on circuit topology and device type. Regarding circuit topology, it is recommended to adopt soft switching topologies such as active clamping flyback or LLC resonance, which can effectively reduce the voltage and current change rate in the switching process and reduce the switching noise by 6- 8 dB. In addition, multi-level technology can be introduced with 3-level or 5-level mating to control the output waveform THD to within 3%. In terms of changing the modulation strategy, such as using adaptive inverter PWM technology to adjust the switching frequency in real time to disperse harmonic energy, the switching loss can be reduced by about 30% with the dead time optimization algorithm. In terms of device selection, SiC MOSFETs with low gate charge (Qg